IL-33-experienced group 2 innate lymphoid cells in the lung are poised to enhance type 2 inflammation selectively in adult female mice - Haya Aldossary; Rami Karkout; Katalina Couto; Lydia Labrie; Elizabeth D. Fixman (Respiratory Research)
Abstract While Th2 adaptive immunity has long been considered to orchestrate type 2 inflammation in the allergic lung, group 2 innate lymphoid cells (ILC2s), with the ability to produce a similar profile of type 2 cytokines, likely participate in lung inflammation in allergic asthma. ILC2s are also implicated in sex disparities in asthma, supported by data from murine models showing they are inhibited by male sex hormones. Moreover, larger numbers of ILC2s are present in the lungs of female mice and are correlated with greater type 2 inflammation. Lung ILC2s exhibit intriguing memory-like responses, though whether these differ in males and females does not appear to have been addressed. We have examined type 2 lung inflammation in adult male and female Balb/c mice following delivery of IL-33 to the lung. While the number of ILC2s was elevated equally in males and females four weeks after exposure to IL-33, ILC2s from female mice expressed higher levels of ST2, the IL-33 cognate receptor subunit, and a larger proportion of ILC2s from females expressed the IL-25 receptor (IL-25R), which has previously been linked to memory-like ILC2 responses in mice. Our data show that the subset of ILC2s expressing IL-25R, upon activation, was more likely to produce IL-5 and IL-13. Moreover, STAT6 was absolutely required for enhanced responsiveness in this model system. Altogether, our data show that enhanced type 2 inflammation in females is linked to durable changes in ILC2 subsets with the ability to respond more robustly, in a STAT6-dependent manner, upon secondary activation by innate epithelial-derived cytokines.